An Analysis of The Students’ Reading Comprehension on Descriptive Text at First Grade SMKS Muhammadiyah Pasir Penyu - Audita, Putri; Wahyuningsih, Destri (ENJEL: English Journal of Education and Literature, 2025)
This study aims to analyze students’ understanding of descriptive texts. Based on observations at First Grade of SMKS Muhammadiyah Pasir Penyu, it was found that some students still had difficulties in comprehending the reading material, especially in identifying main ideas, detailed information, and vocabulary in the text. In addition, the lack of self-confidence also influenced how they understood English texts. This research is a qualitative descriptive study. The participants of this study were 16 first-grade students of SMKS Muhammadiyah Pasir Penyu in the academic year 2025/2026. Data were collected through tests and observation. The researcher gave 20 multiple-choice questions based on indicators of descriptive text reading comprehension, such as recognizing the main idea, word meaning, explicit and implicit information. The data were analyzed by calculating the average score and the percentage of students’ performance. The results of this study are expected to give a clear picture of how well students understand reading texts and can be used as a reference for teachers to improve the quality of English learning in the classroom. The classification of the students’ scores in meeting 1 shows that 12.5% of the students were categorized as excellent, 12.5% as good, 81.25% as fair, and 50% as poor. This indicates that the majority of the students were still in the fair category, with a significant portion also falling under the poor category. Therefore, the average result of students' reading comprehension in descriptive text during the first meeting is categorized as fair. In meeting 2, there was a slight improvement in the students' performance. 12.5% of the students were in the excellent category, 56.25% in the good category, and 81.25% remained in the fair category. This data suggests that although many students were still categorized as fair, more students were able to move into the good and excellent categories compared to the previous meeting. Thus, the overall result in meeting 2 is categorized as good. In meeting 3, the students showed significant progress. A total of 25% of students were categorized as excellent, while 75% were in the good category. There were no students left in the fair or poor categories, which indicates that their understanding of descriptive texts had improved considerably. Therefore, the result of meeting 3 is also categorized as good. Based on the results from meeting 1, 2, and 3, it can be concluded that the reading comprehension ability of the first-grade students of SMKS Muhammadiyah Pasir Penyu in the academic year 2025/2026 has improved. The average score obtained was 65%, which is categorized as good. This shows that through continuous practice and guidance, students were able to develop a better understanding of descriptive texts over time.